The Influence of Person Organization Fit (P O Fit) and Work Environment on Turnover Intention Mediated by Organizational Commitment of Gen Z Employees at PT. Asahi Sukses Industri - Octaviana, Fany; Setyaningrum, Retno Purwani (BASKARA : Journal of Business and Entrepreneurship, 2024)
Employee turnover intention is an important thing that needs to be considered in every company. Companies must be able to reduce the turnover rate which increases over time. Turnover intention has a big impact on the sustainability of company performance. So, companies must be able to properly maintain human resources. Employee performance is very important to improve company performance and employee performance because every business requires quality, innovative and creative human resources to be able to compete with its competitors. The aim of this research is to determine the direct and indirect influence between the variables Person Organizational Fit (P O Fit) and Work Environment mediated by Organizational Commitment on Turnover Intention. This research was conducted using a quantitative approach, the respondents were employees of PT. Asahi Sukses Industri, totaling 57 employees with Saturated sampling. The analytical method used in this research is Partial Least Square (PLS) using the SmartPLS version 3.0 program. The research results show that Person Organization Fit (P O Fit) has a significant effect on Turnover Intention with a t-statistic value (4.932 1.96), Work Environment has an insignificant effect on Turnover Intention with a t-statistic value (0.735 1.96), Organizational Commitment has an insignificant effect on Turnover Intention with a t-statistic value (0.196 1.96), Person Organization Fit (P O Fit) has a significant effect on Organizational Commitment with a t-statistic value (2.730 1.96), Work Environment has a significant effect on Organizational Commitment has a t-statistic value (2.915 1.96), Personnel Organization Fit (P O Fit) which is mediated by Organizational Commitment has an insignificant effect on Turnover Intention with a t-statistic value (0.172 1.96), Work Environment which is mediated by Organizational Commitment has an effect not significant for Turnover Intention with a t-statistic value (0.175 1.96).